Interactive effects of pH and aluminum on the secretion of organic acid anions by roots and related metabolic factors in Citrus sinensis roots and leaves. (July 2020) - Yang, Tao-Yu; Qi, Yi-Ping; Huang, Hui-Yu; Wu, Feng-Lin; Huang, Wei-Tao; Deng, Chong-Ling; Yang, Lin-Tong; Chen, Li-Song
Abstract: Low pH and aluminum (Al)-toxicity often coexist in acidic soils. Citrus sinensis seedlings were treated with nutrient solution at a pH of 2.5, 3.0, 3.5 or 4.0 and an Al concentration of 0 or 1 mM for 18 weeks. Thereafter, malate, citrate, isocitrate, acid-metabolizing enzymes, and nonstructural carbohydrates in roots and leaves, and release of malate and citrate from roots were measured. Al concentration in roots and leaves increased under Al-toxicity, but it declined with elevating nutrient solution pH. Al-toxicity increased the levels of glucose, fructose, sucrose and total soluble sugars in leaves and roots at each given pH except for a similar sucrose level at pH 2.5–3.0, but it reduced or did not alter the levels of starch and total nonstructural carbohydrates (TNC) in leaves and roots with the exception that Al improved TNC level in roots at pH 4.0. Levels of nonstructural carbohydrates in roots and leaves rose with reducing pH with a few exceptions with or without Al-toxicity. A potential model for the possible role of root organic acid (OA) metabolism (anions) in C. sinensis Al-tolerance was proposed. With Al-toxicity, the elevated pH upregulated the OA metabolism, and increased the flow of carbon to OA metabolism, and the accumulation of malate and citrate in roots and subsequent release of them, thus reducing root and leaf Al and hence eliminating Al-toxicity. Without Al-toxicity, low pH stimulated the exudation of malate and citrate, an adaptive response of Citrus to low pH. The interactive effects of pH and pH on OA metabolism were different between roots and leaves. Graphical abstract: Image 1 Highlights: Increasing nutrient solution pH from 2.5 to 4.0 alleviated Citrus Al-toxicity. With Al-stress, high pH increased root accumulation and malate and citrate. With Al-stress, high pH increased secretion of malate and citrate from roots. Without Al-stress, low pH induced secretion of malate and citrate from roots. Malate and citrate secretion played a role in Citrus Al- and acid-tolerance.